Differential Effects of REM Sleep on Emotional Processing: Initial Evidence for Increased Short-term Emotional Responses and Reduced Long-term Intrusive Memories. Issue 1 (2nd January 2021) - Werner, Gabriela G.; Schabus, Manuel; Blechert, Jens; Wilhelm, Frank H.
ABSTRACT: Background : Rapid eye movement (REM) sleep has been postulated to facilitate emotional processing of negative stimuli. However, empirical evidence is mixed and the conditions under which higher amounts of REM sleep lead to decreased or increased emotional responses are unclear. We proposed that the time course between REM sleep and measurement of emotional responses is a crucial factor and hypothesized that more REM sleep will enhance emotional responses shortly after sleep, but will lead to decreased emotional responses in the long-term. Participants and Methods : Seventy-six healthy young women watched negative and neutral pictures before a polysomnographically-recorded nap including three different groups (1: no REM sleep, 2: REM sleep awakening, 3: REM sleep). Short-term emotional responses were measured using aversiveness ratings of negative pictures; aversiveness ratings of intrusive picture memories on the three subsequent evenings were used to measure long-term emotional responses. Results : For short-term emotional responses, no significant interaction indicating group differences was found. However, we found correlations between longer REM sleep duration and higher aversiveness ratings of negative pictures. In contrast, lower aversiveness of intrusive picture memories after two days was found in participants with a full REM sleep period compared to individuals without REM sleep. Correlational analyses also supported this pattern of results. Conclusions : Results suggest that REM sleep may increase reactivity to emotional stimuli in the short-term and this effect of REM sleep appears to facilitate emotional processing during subsequent nights leading to reduced intrusive picture memories in the long-term.